Defining the Rules of Engagement: Legal and Ethical Standards in Cyber Conflict - Tsotniashvili, Zaza (Universitas Andalas, 2024)
In an increasingly digitized world, cyber conflicts are emerging as a critical domain of modern warfare and international relations. This paper examines the legal and ethical standards that govern cyber conflict, aiming to define clear rules of engagement. Through a detailed analysis of current international laws, national legislation, and ethical theories relevant to cyber operations, this research identifies gaps and challenges in the existing frameworks. Case studies of notable cyber incidents illustrate the practical implications of these legal and ethical standards. The study proposes a set of refined rules of engagement designed to address these deficiencies, ensuring ma ore coherent and consistent application of legal and ethical principles in cyber conflict. The findings suggest that while international consensus and cooperation are crucial, there is also a need for dynamic and adaptable rules that can keep pace with rapid technological advancements. This paper contributes to the growing discourse on cyber conflict by providing a comprehensive understanding of the legal and ethical dimensions and offering actionable recommendations for policymakers, legal experts, and cybersecurity practitioners.